Improved line-of-sight trajectory tracking control of under-actuated AUV subjects to ocean currents and input saturation. (15th February 2019) - Xia, Yingkai; Xu, Kan; Li, Ye; Xu, Guohua; Xiang, Xianbo
Abstract: This paper addresses the design of an improved line-of-sight (LOS) based adaptive trajectory tracking controller for an under-actuated AUV subjects to highly coupled nonlinearities, ocean currents-induced uncertainties, and input saturation. The influences of ocean currents on the AUV are expressed in a comprehensive way such that both the kinematic and dynamic models of AUV are established with ocean currents. Extended disturbance observers (EDO) are utilized to estimate the ocean currents-induced uncertainties as well as their time-derivatives. An improved LOS guidance law is designed by introducing an auxiliary variable to the conventional LOS, and utilizing extended disturbance observers to estimate the ocean current-induced disturbances in the kinematic model. EDO-based adaptive terminal sliding mode control method is employed for dynamic control to improve the tracking performance and converging rate. In addition, the influence of actuator saturation is weakened by anti-windup compensator. Rigorous theoretical analysis and extensive simulation studies demonstrate that the proposed approach has good tracking accuracy, stability, and anti-jamming ability, thus leading to satisfying trajectory tracking control.